La familia multiespecie en el DIPR: propuesta de regulación normativa del cuidado personal de los animales de compañía - Mingorance, Paula (2022)
The present work seeks to outline norms of private international law that regulate the personal care of companion animals in cases of divorce and separation of cohabiting unions. For which, the subject will be addressed starting from general basic concepts, to later deepen into specific issues building, in order to build the different theoretical links that will provide the basis for the proposed normative regulation. In this regard, the legal definition of the concept of family, its historical evolution and the current scenario will be provided, to then conceptualize the notion of multispecies family. Likewise, the article will present the current legal treatment that the Civil and Commercial Code of the Nation offers to non-human animals - according to which judges must resolve the concrete cases that come to their knowledge -, in order to subsequently support the position that non-human animals are holders of rights, such as the right to equality, the right to life, the right to freedom, the right to their habitat, the right to health system, the right to dignity and, the right that concerns us in this paper, the "right to family", justifying the position in doctrine and jurisprudence. In addition, the work will describe the theoretical basis of private international law, specifically with respect to the areas of applicable law and competent jurisdiction. From the foregoing, the regulation of the aforementioned institute will be studied, so as to integrate the previously established knowledge. Finally, the article will conclude with a review and critique of various current rules and draft laws on international comparative law, with a view to setting the stage for a subsequent normative construction that regulates the substantive law on the subject